Au-Bi-Te MINERALIZATION OF THE KONTAKTOVYI STOCK IN NORTHEAST RUSSIA - Sidorov V.A.; Volkov A.V.; Sidorov A.A.; Wolfson A.A. (My University, 2007)
In recent years, interest in gold deposits in granitoid intrusions has been boosted by the successful development of gold deposits in Alaska and Australia, such as Fort Knox (>350 t), Pogo (150 t), Dublin Gulch (>100 t), and Tefler (>500 t). At present, more than 30 deposits of this type have been discovered in various metallogenic belts of Northeast Asia. Many of these deposits can be large and superlarge objects. In previous publications, we discussed examples of ore occurrences and deposits in the Yana–Kolyma metallogenic belt and the perivolcanic zone of the Okhotsk–Chukot volcanogenic belt (OCVB). However, some ore occurrences associated with granite porphyry stocks are confined to sedimentary sequences at the base of the OCVB. These stocks were likely to be emplaced in the course of the tectonomagmatic cycle of the Late Jurassic–Early Cretaceous Uda–Murgal island-arc volcano-plutonic belt. The most promising ore occurrence was discovered in 2005 in the Kontaktovyi (i.e., Contact) granite porphyry stock.